Atomic layer etching of GaN and AlGaN using directional plasma-enhanced approach. (25th May 2017) - Ohba, Tomihito; Yang, Wenbing; Tan, Samantha; Kanarik, Keren J.; Nojiri, Kazuo
Abstract: The directional atomic layer etching (ALE) of GaN and AlGaN has been developed. The GaN ALE process consists of cyclic Cl2 plasma chemisorption and Ar ion removal. The etch per cycle (EPC) was 0.4 nm within the self-limiting regime, which is 50 to 100 V. The root-mean-square surface roughness R RMS was 0.6 nm, which was improved from an initial roughness of 0.8 nm. For AlGaN ALE, BCl3 was added to the chlorine step to obtain a smooth surface with R RMS of 0.3 nm and stoichiometry similar to the initial sample. The ultra smooth surface obtained by etching is promising for use in next-generation power devices.